Rethinking historical jurisprudence - Samuel, Geoffrey, 1946- (Rethinking law, 2022)
This stimulating book considers the ways in which historical jurisprudence deserves to be rethought, arguing that there is much more to the history of legal thought than the ideas, and ideology, of the nineteenth and early twentieth century jurists, such as Karl von Savigny and Sir Henry Maine.